2009
DOI: 10.1007/s00228-009-0756-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with success of market authorisation applications for pharmaceutical drugs submitted to the European Medicines Agency

Abstract: 0001).Stepwise regression analysis revealed that company size and SA compliance were independent predictors of outcome. The proportion of the MAAs that had received SA increased from 22% in 2004 to 47% in 2007. Company size and product type were associated with the frequency of requesting SA (26, 33 and 46% for small, medium-sized and large companies, respectively; 16, 39 and 48% for known chemical substances, new chemical substances and biologics, respectively). Factors related to compliance with SA were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 7 publications
3
61
0
Order By: Relevance
“…There were too few MAAs to gain insights about the relevance of these three endpoint properties in accelerated reviews. Analyses of MAAs have found that obtaining and following scientific advice provided by the EMA was associated with a positive approval outcome [15,29]; however, we did not explore the role of scientific advice in influencing the quality of the dossier or the outcome of the review process for this cohort. Although the basis for the approval of a new medicine is a favorable risk-benefit profile, we focused on efficacy endpoints and did not address the safety issues of this cohort as an influence in MAA outcome.…”
Section: Discussionmentioning
confidence: 91%
“…There were too few MAAs to gain insights about the relevance of these three endpoint properties in accelerated reviews. Analyses of MAAs have found that obtaining and following scientific advice provided by the EMA was associated with a positive approval outcome [15,29]; however, we did not explore the role of scientific advice in influencing the quality of the dossier or the outcome of the review process for this cohort. Although the basis for the approval of a new medicine is a favorable risk-benefit profile, we focused on efficacy endpoints and did not address the safety issues of this cohort as an influence in MAA outcome.…”
Section: Discussionmentioning
confidence: 91%
“…The contribution of regulators in scientific advice/protocol assistance increases the chance of a successful development of the orphan medicinal product [4]. The experience with authorizations of medicines for rare diseases shows that even though marketing authorization applicants are dealing with extremely complicated development programs and regulatory authorities are faced with limited data in comparison with frequent diseases, it is still feasible to bring to the market safe and effective products for rare diseases in ratios that are comparable with nonrare diseases [5,6].…”
Section: Regulatory Supportmentioning
confidence: 99%
“…The scientific advice from EU National Authorities and/or EMA is strongly encouraged, given the apparent association between the compliance with scientific advice and the success of the application. 27 Indeed, a relevant result in one subgroup will not be accepted as proof of efficacy in the absence of positive outcomes in the whole study population. Moreover, the possible uncertainties raised about the study should be ruled out, allowing the benefit to outweigh the risk.…”
Section: Resultsmentioning
confidence: 99%